2009
DOI: 10.1021/jf902411c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Selenomethionine Supplementation on Growth Performance, Meat Quality and Antioxidant Property in Yellow Broilers

Abstract: This study was conducted to investigate the effects of dietary selenomethionine (Se-Met) supplementation on growth performance, meat quality and antioxidant property in male broilers. A total of 800 43-day-old Lingnan yellow male broilers were randomly allotted to 5 dietary treatments with four replicates of 40 birds for a period of 3 weeks ad libitum. Final BW and weight gain of birds significantly increased by Se-Met supplementation at the 0.225 mg/kg level (P < 0.05). The addition of Se-Met significantly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
54
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 25 publications
11
54
0
Order By: Relevance
“…L-Selenomethionine supplementation significantly (p<0.05) increased T-AOC in the kidney, pancreas, and breast muscle ( Table 8). The results were in agreement with previous reports [9,34]. These findings suggested that Se-Met improved antioxidative status of broilers by elevating activities of antioxidant enzymes and concentrations of antioxidant and reducing the metabolic product of lipid peroxides of MDA concentration, and also implicated that Se-Met supplementation may have a beneficial effect on oxidative stability and extended shelf life of fresh meat than SS.…”
Section: Selenomethionine Treatments Versus Sodium Selenitesupporting
confidence: 93%
See 1 more Smart Citation
“…L-Selenomethionine supplementation significantly (p<0.05) increased T-AOC in the kidney, pancreas, and breast muscle ( Table 8). The results were in agreement with previous reports [9,34]. These findings suggested that Se-Met improved antioxidative status of broilers by elevating activities of antioxidant enzymes and concentrations of antioxidant and reducing the metabolic product of lipid peroxides of MDA concentration, and also implicated that Se-Met supplementation may have a beneficial effect on oxidative stability and extended shelf life of fresh meat than SS.…”
Section: Selenomethionine Treatments Versus Sodium Selenitesupporting
confidence: 93%
“…However, in the present study, GSH-Px activities of liver, kidney and pancreas were higher (p<0.05) in the SS group than those in the D-Se-Met group; but no differences were detected with respect to GSH-Px activities in serum and tissues between the SS and L-Se-Met groups ( Table 4). The results were consistent with those of Zhan et al [9], Payne and Southern [33] and Jiang et al [34]. The lower GSH-Px activity in broilers fed Se-Met diet compared broilers fed SS diet are probably because that Se, regardless Values are means±SE, n=5.…”
Section: Selenomethionine Treatments Versus Sodium Selenitesupporting
confidence: 91%
“…Our particular interest is the potential regulation of TrxR1, SelP, and SelW in broilers by Se supplementing due to their potential relevance to antioxidant defense mechanisms. It was reported that organic Se was more effective in increasing antioxidant property than inorganic Se (Mahan and Parrett 1996;Payne and Southern 2005;Jiang et al 2009;Wang et al 2011a, c). However, data from the present study indicated that the SS supplemented diet increased more serum (P < 0.05) and liver (P < 0.01) SelP concentrations as well as liver (P < 0.01) and kidney (P < 0.01) TrxR1 activities than the d-Se-Met supplemented diet; while the activity of liver and kidney TrxR1 was significantly (P < 0.01) lower in the l-Se-Met-supplemented group than in the SS-supplemented group (Tables 3 and 4).…”
Section: Resultsmentioning
confidence: 98%
“…In fact, the activities of serum GSH-Px, SOD and total antioxidant capacity were significantly higher in selenium yeast than sodium selenite-fed chickens [102]. Similarly, dietary Se-Met significantly elevated T-AOC, GPX, T-SOD, CAT activities, contents of GSH and reduced carbonyl protein content in chicken breast muscle [103]. It was shown that dietary organic Se significantly increased the Se content and the activities of CAT and SOD, but decreased the MDA content in chicken breast muscle at 42 days of age [104].…”
Section: Seleniummentioning
confidence: 91%